Rhetorical strategies in Chinese and English talk show humor: a comparative analysis - Tianli, Zhou; Chen, Shiyue (Frontiers in Psychology, 2024)
Humor is a kind of cognitive psychology activity, and it is diverse among individuals. One of the main characteristics of talk shows is to produce humorous discourse to make the audience laugh; however, rare studies have made a deeper comparative investigation on the rhetorical strategies in different language humorous utterances. Therefore, the current study adopted a mixed method of sequential explanatory design to identify the types of rhetorical strategies in the monolog verbal humor of Chinese and English talk shows, examine their similarities and differences. Two hundred monolog samples from 2016 to 2022, which consisted of 100 monologs of Chinese talk shows (CTS) and 100 monologs of English talk shows (ETS), were downloaded from the internet as language corpus. Berger’s theory was adopted to identify the types of rhetorical strategies. Based on the obtained findings, this study found that both language talk show hosts use a variety type of rhetorical strategies to produce humorous discourse. The comparison of similarities and differences revealed that the most frequently used rhetorical strategies in both talk shows were almost similar (e.g., satire, exaggeration, facetiousness, and ridicule), but the percentage of usage of these various rhetorical strategies in both talk shows was slightly different. Interestingly, misunderstanding occurred 20 times in CTS but was not found in ETS. Meanwhile, simile and personification were used more often in ETS. Conclusively, this study contributes valuable insights on the use of different types of rhetorical strategies to create verbal humor in different language contexts.